PENGARUH PELAYANAN PUBLIK TERHADAP KEPUASAN MASYARAKAT DI KANTOR KELURAHAN TUALANG KECAMATAN PERBAUNGAN KABUPATEN SERDANG BEDAGAI - Linjasmin Iska Dachi; Sepma Wati Dakhi; Elazhari (LPPM Universitas Cipta Mandiri, 2024)
Community satisfaction is a measure of the extent to which the public services that the government has distributed to the community are good or not. People who are satisfied with the services they receive will generate trust in the government and other public institutions. Quantitative research methods are defined as research methods that are based on correct knowledge only from natural sciences that are used in research on certain populations or samples and sampling techniques using random sampling techniques, data collection using research instruments, data analysis that is associative research/causal relationships. . The research location was research carried out at the Tualang Village Office, Perbaungan District, Serdang Bedagai Regency. with problems regarding the influence of Public Services on Community Satisfaction at the Tualang Village Office, Perbaungan District, Serdang Bedagai Regency. Public services have a significant effect on community satisfaction at the Tualang Village Office, Perbaungan District, Serdang Bedagai Regency. This can be explained that if public services are implemented according to good standard operating procedures and the services provided are in line with community expectations, then the community will be satisfied with the services provided and the level of public trust in public services will increase.